Facile Synthesis of Benzocyclohepta[1, 2‐c]pyrazoles Starting from Morita–Baylis–Hillman Adducts Via an Intramolecular Friedel‐Crafts Alkenylation. (16th June 2015) - Yu, Jin; Lee, Sangku; Moon, Hye Ran; Kim, Jae Nyoung
<x xml:space="preserve">Abstract</x>